ANALYSIS OF LEARNING HISTORY OF ISLAMIC CULTURE (SKI) BASED ON 2013 CURRICULUM - Zuhriah Zuhriah; Sedya Sentosa (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
The purpose of this study was to determine the understanding of SKI teachers towards the 2013 curriculum, teacher plans and practices, evaluation, supporting and inhibiting factors in SKI learning based on the 2013 curriculum on the topic of Islamic Civilization of the Umayyad Daula in Damascus for class X IPS MAN 1 Bungo. This research is a qualitative descriptive study. The sampling method used was purposive sampling. Data collection was carried out by interviews, observation, and document analysis. The results of the study show that SKI teachers' understanding of the 2013 curriculum is quite good but still needs to be improved; RPP is guided by the 2013 curriculum guidelines; teaching practice according to the lesson plan prepared by the teacher which consists of three stages, namely introduction, core activities covering 5M, and closing. These three stages are carried out by SKI teachers to instill character values in students; SKI learning evaluation includes cognitive, affective, and psychomotor aspects; Supporting factors in teaching SKI include complete facilities, curriculum 2013 training for teachers, and complete learning resources.